منهج ابن عادل في توجيه القراءات في تفسيره اللباب في علوم الكتاب دراسة تحليلة - Rohaizan, Baru; Mohamed Fathy, Mohamed Abdelgelil; Wafi Yahya, Saleh Yahya (2019)
The science of Taujih reveals the approach of Qira’at (recitation) and its connection with Arabic grammar and language both in analysis and approval for the valid aspects of an accurate recitation and its agreement with language. It is a great field that consists of many other sciences. At times, the science of Taujid reveals the knowledge of grammar or exegesis of the Qur’an, providing evidences from Qur’anic verses, Arab poems and plays, and speeches, as well as the rules of Tajweed (recital of the Qur’an). Therefore, this article uses analytical method to investigate the concept of the science of Taujih and its importance, as well as identify the recitation approach adopted by Son of adel hanbali. Amongst the most important findings of this study are: the science of Taujih is one of the most important sciences used to establish the validity of recitations and understanding of the Qur’an as well as explanation of the meaning of Qur’anic verses, and all recitations have the same status in terms of narration and are different only in terms of meanings.